An analysis of spring bird migration phenology in Kansas - Patterson, Judd (Kansas State University, 2008)
In late summer and fall, many migratory birds journey south from the North American Great Plains to spend the winter in locations with greater food availability. As spring returns, a combination of genetics and environmental cues trigger these birds to return north to their breeding grounds. Several bird migration phenology studies from Europe, Australia, and the eastern/northern United States have discovered that some bird species are returning earlier in the spring, a change that has often been correlated with a warming climate. This study aimed to be the first to analyze possible changes in both spring bird migration phenology and regional spring climate change in Kansas. First arrival dates (FADs) were collected for thirty bird species, resulting in a database with over 6,000 FAD entries. For northeast Kansas, 1997-2007 median arrival dates were calculated and compared to dates published by Dr. Richard Johnston in 1965. In southcentral Kansas, 1997-2007 and 1947-1967 median arrival dates were calculated and compared. Temperature data from spring (February through May) were also obtained from the National Climate Data Center's United States Historical Climatology Network for all stations within northeast and south central Kansas and temporal trends were analyzed with linear regression analysis. A comparison between median arrival dates in northeast Kansas found that eleven species had altered their arrival date by a potentially significant number of days. Nine of these had advanced their arrival and two showed a delay. In south central Kansas, nine species were shown to have statistically significant differences in median arrival dates between time periods. Six of these showed an advance and three showed a delay. Five species showed the same trend between both regions, with four arriving earlier by an average 9.4 days and one delaying by an average of 4.5 days. Temperature trends for both subregions in Kansas showed significant warming of 1.8-2.6°F (1.0-1.4°C) over the last century, with the largest warming observed in February and associated strongly with increasing minimum temperatures. The results from this study provide the first evidence that some bird species have recently altered the timing of their arrival in Kansas, with a greater shift toward earlier arrival dates. While the majority of these shifts were correlated with spring warming in Kansas, additional research is necessary to determine the precise cause(s) of these phenological shifts. Still, given existing literature and Intergovernmental Panel on Climate Change predictions for continued warming in the next century, continued alterations to bird migration phenology seem likely.
Keywords: Bird migration; Phenology; Kansas; Median arrival date; Climate change; Spring; Biology, Ecology (0329); Geography (0366)